2018
DOI: 10.3389/fmicb.2018.01139
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Responses of the Diazotrophic Microbiome to Elevated CO2 in Two Rice Cultivars

Abstract: The species-specific responses of plant growth to elevated atmospheric CO2 concentration (eCO2) could lead to N limitation and potentially influence the sustainability of ecosystem. Questions remain unanswered with regards to the response of soil N2-fixing community to eCO2 when developing high-yielding agroecosystem to dampen the future rate of increase in CO2 levels and associated climate warming. This study demonstrates the divergent eCO2 influences on the paddy diazotrophic community between weak- and stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…N cycling was also stimulated by eCO 2 , especially in terms of the increased absolute abundance of nifH. Our result was consistent with the findings of studies conducted in other soil ecosystems, such as rice ecosystems [81] but differed from the findings of one study, which reported no effect of eCO 2 on N fixation [82]. The higher absolute abundance of nifH under eCO 2 fumigation indicated high demand for N and high metabolic activity.…”
Section: Changes In Microbial Functions Under Ecosupporting
confidence: 85%
“…N cycling was also stimulated by eCO 2 , especially in terms of the increased absolute abundance of nifH. Our result was consistent with the findings of studies conducted in other soil ecosystems, such as rice ecosystems [81] but differed from the findings of one study, which reported no effect of eCO 2 on N fixation [82]. The higher absolute abundance of nifH under eCO 2 fumigation indicated high demand for N and high metabolic activity.…”
Section: Changes In Microbial Functions Under Ecosupporting
confidence: 85%
“…The experimental FACE platform was located in Zongcun Village (119 • 42 0 E, 32 • 35 5 N), Yangzhou City, Jiangsu Province (Figure 1; Yu et al, 2018). The long-term experimental platform with a rice-wheat rotation crop system started in 2004.…”
Section: Study Site and Experimental Designmentioning
confidence: 99%
“…The long-term experimental platform with a rice-wheat rotation crop system started in 2004. From 2010, the rice-wheat rotation system was changed to a rice-fallow system (Yu et al, 2018). The region has a north subtropical monsoon climate with a mean annual temperature of 16 • C and a mean annual precipitation of 900-1,000 mm.…”
Section: Study Site and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations